The Transformation of Jayengrana Dance from the Perspective of Anthony Giddensâs Structuration Theory - Sumiati, Lilis (ASPENSI in Bandung, Indonesia, 2014)
ABSTRACT: Transformation in structuration theory is caused by two things which are the roles of the agents and the interest in system construction purpose. Change of structure in the transformation, according to Anthony Giddens (2011), is limited to the actions of the agents to modify the existing structure. It means that the initial structure is not then removed, but still acts as the main basis. The application of the structuration theory on dance can be found in the case of transformation of âJayengranaâ dance which has endured significant changes after its proliferation. âJayengranaâ dance is one of dancing repertoires in Sumedangâs âwayangâ dance genre in West Java, Indonesia. The potential in âJayengranaâ dance is shown in its phenomenal proliferation. The level of the proliferation can be seen not only in local and regional level, but also in international one. The agent involving in this phenomenon of the transformation of âJayengranaâ dance is R. Ono Lesmana Kartadikusumah (Ono) in Sumedang and Iyus Rusliana in Bandung. The agents of change for âJayengranaâ dance give their creativity which has modifying qualities aiming to fulfill the systemâs needs, aesthetic demands, and todayâs theatrical elements of dancing performances. Finally, âJayengranaâ dance, as a treasure of âwayangâ dance Sumedang style, must be conserved in terms of its originality and also can be a model for the dance which will always be open for the reconstruction.KEY WORDS: Transformation, structuration theory, âJayengranaâ dance, Anthony Giddens, R. Ono Lesmana Kartadikusumah (Ono) and Iyus Rusliana, and agent of change.About the Author: Lilis Sumiati, M.Sn. is a Ph.D. Student at the Faculty of Humaities UNPAD (Padjadjaran University), Jalan Raya Sumedang-Bandung, Jatinangor, West Java; and also as a Lecturer at the STSI (Indonesiaâs Art College) Bandung, West Java, Indonesia. Corresponding author is: lilissumiati1411@yahoo.comHow to cite this article? Sumiati, Lilis. (2014). âThe Transformation of Jayengrana Dance from the Perspective of Anthony Giddensâs Structuration Theoryâ in TAWARIKH: International Journal for Historical Studies, Vol.5(2) April, pp.223-236. Bandung, Indonesia: ASPENSI [Asosiasi Sarjana Pendidikan Sejarah Indonesia] and UVRI [Universitas Veteran Republik Indonesia], ISSN 2085-0980.Chronicle of the article: Accepted (February 1, 2014); Revised (March 3, 2014); and Published (April 28, 2014).